Social Trust and Economic Governance - HUANG, Fali (Institutional Knowledge at Singapore Management University, 2004)
The paper investigates the dynamic relationship between social trust and economic governance using a principal-agent model with stochastic returns. To mitigate the inherent moral hazard problem both intrinsic and extrinsic incentives are useful. The cooperative tendency of an agent measures his intrinsic discipline against shirking, the distribution of which characterizes social trust in society. The economic governance methods include direct monitoring and efficiency wage. The main results are the following. An agent with a higher cooperative tendency needs less monitoring and a lower wage to make effort, which brings higher profit for the principal. But competition among principals for more cooperative agents drains away the extra profit and passes it on to the agent as a sign-in bonus. So an agent with a higher cooperative tendency ends up earning a higher total income. In the short run when cooperative tendencies are fixed, the distribution of economic governance intensity in the economy is determined by social trust. In the long run when cooperative tendencies are endogenously formed to maximize an agent’s lifetime utility, both social trust and economic governance are determined by fundamentals such as the costs of monitoring, screening, and investing in cooperative tendency. In the steady state, social trust increases in monitoring cost and decreases in screening and investing costs. An important insight the paper delivers is that principals always benefit from a lower monitoring cost but not necessarily from a higher social trust. Both downward and upward movement of social trust and economic governance, once started, would continue monotonically. Their relative strength across societies is preserved or reinforced over time.